Differences of Clinical and Laboratory Presentation in Positive and Negative Acid Fast Bacilli Pulmonary Tuberculosis Patients - Amila Hanifan Muslimah; ArtoYuwono Soeroto; Enny Rohmawaty (Althea Medical Journal, 2016)
Background: Based on bacteria status, tuberculosis is classified into positive and negative acid fast bacilli. This study was conducted to determine the differences of clinical and laboratory presentation in positive and negative acid fast bacilli pulmonary tuberculosis patients.Methods: This study was an observational analytic study with a cross-sectional approach which used 338 medical records of patients with pulmonary tuberculosis at Direct Observational Treatment Short-course(DOTS) clinic Dr. Hasan Sadikin General Hospital from January to December 2012. Data collected were clinical and laboratory presentation for analytic study. Data about comorbid were collected for descriptive data.Results: From 338 medical records, 223 were medical records of patients with pulmonary tuberculosis and 105 medical records of patients with comorbid. Twenty (18.01%) comorbid were Human Immunodeficiency Virus (HIV). Acid fast bacilli negative was more (121, 51.9%) than acid fast bacilli positive (112, 48.1%). Differences of laboratory presentation were found in hemoglobin count (p=0.037), red blood cell count (p=0.022), and erythrocyte sedimentation rate (p=0.006) and not found in white blood cell count (p=0.073), thrombocyte count (p= 0.766), serum glutamic oxaloacetic transaminase (p=0.169), and serum glutamicpyruvic transaminase (p=0.309). Difference of clinical manifestation was not found in fever (p=1), cough (p=0.608), night sweats (p=0.09), dyspnea (p=0.210), and weight loss (p=0.269).Conclusions: Differences between acid fast bacilli positive and negative are found in hemoglobin, red blood cell, and erythrocyte sedimentation rate laboratory examination. The highest comorbid of pulmonary tuberculosis patient is HIV. [AMJ.2016;3(2):286–5]DOI: 10.15850/amj.v3n2.786